2023
DOI: 10.3389/fnins.2023.1119200
|View full text |Cite
|
Sign up to set email alerts
|

Can visual cortex non-invasive brain stimulation improve normal visual function? A systematic review and meta-analysis

Abstract: ObjectiveMultiple studies have explored the use of visual cortex non-invasive brain stimulation (NIBS) to enhance visual function. These studies vary in sample size, outcome measures, and methodology. We conducted a systematic review and meta-analyses to assess the effects of NIBS on visual functions in human participants with normal vision.MethodsWe followed the PRISMA guidelines, and a review protocol was registered with PROSPERO before study commencement (CRD42021255882). We searched Embase, Medline, PsychI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 88 publications
0
7
0
Order By: Relevance
“…While both tDCS and tRNS are implicated in the reduction of visual crowding (Bello et al, 2023), it is also possible that the improvement due to brain stimulation found in the current study was not strictly driven by reduced visual crowding. Although peripheral RSVP reading tasks are beholden to visual crowding, they do not inherently measure visual crowding.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…While both tDCS and tRNS are implicated in the reduction of visual crowding (Bello et al, 2023), it is also possible that the improvement due to brain stimulation found in the current study was not strictly driven by reduced visual crowding. Although peripheral RSVP reading tasks are beholden to visual crowding, they do not inherently measure visual crowding.…”
Section: Discussionmentioning
confidence: 73%
“…Applying non-invasive transcranial electrical stimulation (tES) to early visual areas can reduce the strength of visual crowding without changing the visual characteristics of the stimulus, enabling better processing of cluttered visual scenes (Bello et al, 2023). The effect of tES on visual crowding has been examined in participants with normal vision (Chen et al, 2021; Contemori et al, 2019; Raveendran et al, 2020) as well as in patients with visual dysfunction, including macular degeneration (Raveendran et al, 2021), and amblyopia (Donkor et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Anodal transcranial direct current stimulation (a-tDCS), a common NIBS technique ( Nitsche and Paulus, 2000 ), has been demonstrated to improve a range of visual functions. Results from a recent meta-analysis illustrated that visual cortex a-tDCS improved contrast sensitivity, visual evoked potential amplitude (an index of cortical excitability), and crowding in peripheral vision among normally sighted individuals ( Bello et al, 2023 ). TDCS involves a weak 1 – 2 mA electrical current delivered through two head-mounted electrodes (the anode and cathode) and induces regional changes in cortical excitability and neurotransmitter concentrations that outlast the duration of stimulation [see Roche et al (2015) for a review].…”
Section: Introductionmentioning
confidence: 99%
“…In summary, a-tDCS of the visual cortex can reduce crowding in peripheral vision ( Spiegel et al, 2012 ; Raveendran et al, 2020 ; Bello et al, 2023 ), and, on this basis, we explored whether a-tDCS could improve peripheral reading in patients with AMD ( Silva et al, 2022 ). A differential effect for English and Chinese writing systems was found whereby there was no improvement for Chinese readers.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence has demonstrated that the tES targeting on the occipital region (Oz) can enhance, preserve, and even restore visual functions in healthy and visually impaired individuals ( 4 ). However, the effects of tES on vision remain inconclusive in the literature [refer to ( 5 ) for a recent systematic review]. This variability may stem from diverse stimulation parameters employed across studies, influencing the neuroplastic aftereffects and the subsequent efficacy of tES.…”
Section: Introductionmentioning
confidence: 99%